Strategi Pembelajaran Menyenangkan Berbasis Lingkungan Di Sekolah Dasar: Pendekatan Kualitatif Dalam Meningkatkan Motivasi Siswa - Prijambodo, Raden Firman Nurbudi; Punggeti, Ratna Novita; Azizah, Lutfiana Fazat (-, 2025)
This study aims to explore fun learning strategies based on the environment to enhance students' motivation in elementary schools. Using a qualitative approach, data were collected through observations, interviews, and documentation in several elementary schools. The findings indicate that utilizing the environment as a learning resource can create more interactive, contextual, and meaningful learning experiences for students. Various strategies, such as direct exploration, educational games, and project-based activities, have been proven to increase students' interest, engagement, and motivation in the learning process. Furthermore, this study emphasizes the crucial role of teachers in designing and implementing enjoyable learning strategies by leveraging the surrounding environment. Support from schools and parents also plays a vital role in the success of these strategies. Therefore, implementing environment-based learning should continue to be developed to create more engaging and effective learning experiences for elementary school students.